2022
DOI: 10.1007/s00464-022-09655-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Inpatient and Outpatient Utilization of Bariatric Surgery

Abstract: Background During the COVID-19 pandemic, deferral of inpatient elective surgical procedures served as a primary mechanism to increase surge inpatient capacity. Given the benefit of bariatric surgery on treating obesity and associated comorbidities, decreased access to bariatric surgery may have long-term public health consequences. Understanding the extent of the disruption of the COVID-19 pandemic to bariatric surgery will help health systems plan for appropriate access. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In the recent past, several studies have quantified this reduction in the number of surgical procedures undertaken for total joint arthroplasty, 37 orthopedic knee procedures, 38 elective hernia repair, 39 and bariatric surgery. 40 Owing to the pandemic-related disruptions, we observed a sharp drop in the number of surgical admissions which required opioid use over the calendar year 2020. However, the trend of decreasing number of surgical admissions associated with opioid usage were identified over the calendar years preceding (2019) and following (2021) the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 91%
“…In the recent past, several studies have quantified this reduction in the number of surgical procedures undertaken for total joint arthroplasty, 37 orthopedic knee procedures, 38 elective hernia repair, 39 and bariatric surgery. 40 Owing to the pandemic-related disruptions, we observed a sharp drop in the number of surgical admissions which required opioid use over the calendar year 2020. However, the trend of decreasing number of surgical admissions associated with opioid usage were identified over the calendar years preceding (2019) and following (2021) the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 91%
“…A national study on 767 hospitals assessing all payer types found that White patients experienced the greatest reduction in elective surgeries, compared to other racial groups, suggesting that the pandemic did not exacerbate racial disparities in elective surgical care [6] . Further studies in bariatric, cardiac, and orthopedic surgical subspecialties revealed that patient populations were more diverse (lessened racial and SES disparities) after the onset of the pandemic for some surgical procedures but less diverse (greater racial and SES disparities) for others [7] , [8] , [9] , [10] . Studies assessing academic general surgery departments, however, showed that male, White, and privately insured patients were more likely to undergo medically-necessary procedures during the pandemic [11] and that patients with higher SES (commercial or non-governmental insurance) were more likely to utilize both in-person and telemedicine visits during the pandemic [12] .…”
Section: Introductionmentioning
confidence: 99%